Sterile sterilization? : does control over the monetary base affect the long-term yield structure? (2018)
This paper provides empirical evidence on how sterilization through Open Market Operations affects the long-term yield structure. From a banking point of view, at least two mechanisms are relevant: (i) a change in the supply of sovereign securities and (ii) a change in the composition of commercial banks- assets. This paper uses a linear regression to identify sterilization surprises. An advantage of the applied method of identifying OMO?s random responses is that sterilization is well defined through observables. Therefore, the orthogonal to the deterministic component of both permanent and temporary OMOs can be recognized through policy variations conditioned on observed characteristics. In such a way, the resulting variables are as good as randomly assigned and can be used to identify causal effects.